INCREASING THE EXPORT POTENTIAL BASED ON THE DEVELOPMENT OF THE MARKET OF UZBEK AGRICULTURAL PRODUCTS (American Journal of Business Management, Economics and Banking, 2023)
Foreign trade processes play an important role in Uzbekistan's international economic relations. The development of foreign trade is carried out directly by increasing the export potential, delivering new products and services to the world market in terms of quantity and quality. Today, it is emphasized in many studies that there is a huge export potential in the agricultural sector. However, one of the problems faced by agricultural producers and product processors can be described as having the necessary information about the foreign market, adapting to innovative and technological changes, and studying the requirements of the international market. This article aims to analyze the role and importance of marketing research in increasing the export potential of agricultural products of Uzbekistan, the processes of formation of the value chain in the sale of products, methods of increasing competitiveness in the international market, and the analysis of existing problems.